Iron Doped Calcium Manganese Oxide Cathode Materials for Aqueous Zinc Secondary Batteries - Gota Asano; Yoshiyuki Kojima (Indonesian Journal of Chemical Research)
In recent years, zinc secondary batteries, which utilize a water-based electrolyte and offer high safety, have attracted attention as post-lithium-ion batteries. Zn has a high specific capacity (820 mAh/g) and a redox potential of -0.76 V (versus the standard hydrogen electrode) as a cathode. Furthermore, combining it with new cathode materials could significantly enhance performance. In particular, layered compounds containing manganese are inexpensive, widely used in industry, and considered promising candidates. This study synthesized calcium manganese oxide with a layered structure and investigated its potential as a cathode material for zinc secondary batteries. It is already known that Ca₂Mn₃O₈ has a layered structure and can be synthesized with a Mn/Ca atomic ratio ranging from 1.5 to 2.5. This research examined the effect of adding Fe and Al to this calcium manganese oxide on battery performance. When Fe was added, the battery capacity increased by 20%, reaching 177 mAh/g compared to the sample without Fe. This increase is believed to result from an increased interlayer distance, promoting the incorporation of structural water and enhancing ion conversion reactions during charge and discharge. However, adding Al was found to have no beneficial effect on battery performance.